Comparison of Eosin, Physiological Saline and Lugol Solutions by Using A Native Method for Detection of All Soil-Transmitted Helminths (STH) - Kaswi, Nurwilda (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
Stunting can be caused by worm disease because it will interfere with the absorption of nutritional intake, especially carbohydrates and protein, in children. World Health Organization (WHO) data in 2021 reported 24% of the world’s population was infected by Soil Transmitted Helminths (STH). Worms belonging to STH are Ascaris lumbricoides, Trichuris trichiura and hookworms (Ancylostoma duodenale and Necator americanus). The diagnosis of intestinal worms is confirmed by microscopic examination of the feces supported by staining. This study aimed to explore and identify eosin, lugol and physiological saline and evaluate their chemical content as staining solutions to prepare stool samples. A total of 5 stool samples divided into 15 microscopic glass slide were successfully obtained from children around Politeknik Muhammadiyah Makassar. Ascaris lumbricoides was most prevalent helminth found in observations by all the three methods (eosin, lugol and physiological saline wet mount preparation). It was also observed that the young (1-10 years) were more infected because we took samples from childrens around the campus Politeknik Muhammadiyah Makassar. However all the three methods, eosin was found to be effective in coloring the egg stage of the STH parasites. Eosin for wet mount smear in examining the stool samples for detection of intestinal helminths may be routinely used which is simple, clarifying observations under the microscope and increasing the contrast between stained worm eggs and the background because these dye is an acidic compound that is able to fluoresce because it contains bromine and fluorescein so that it can color the cytoplasm and provide a contrast effect so that the boundaries between cells can be observed clearly.